2020
DOI: 10.1021/acscatal.0c00936
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Local and Global Structures of Single Co Atoms for a Superior Oxygen Reduction Reaction

Abstract: The ability to tune both local and global environments of a singlemetal active center on a support is crucial for the development of highly robust and efficient single-atom electrocatalysts (SAECs) that can surmount both thermodynamic and kinetic constraints in electrocatalysis. Here, we designed a core−shellstructured SAEC (Co 1 -SAC) with superior oxygen reduction reaction (ORR) performance. Co 1 -SAC consists of a locally engineered single Co-N 3 C 1 site on a Ndoped microporous amorphous carbon support env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(87 citation statements)
references
References 47 publications
0
87
0
Order By: Relevance
“…The research revealed that the Fe−N 2 site was superior to the Fe−N 4 site because it had a lower interaction with *O 2 and *OH intermediates and accelerated electron transport [30] . Compared with the Co−N 2 C 2 and Co−N 4 sites, the ORR process proceeding over the Co−N 3 C 1 site has been revealed more energetically favorable [31] . The near‐Fermi electronic states of the Co−N 3 C 1 structure was distinct from that of the Co−N 2 C 2 and Co−N 4 structures, which not only facilitated the electronic hybridization with O 2 but also promoted the subsequent protonation of adsorbed O 2 *, thereby forming OOH*.…”
Section: Identification Of Active Sites For M−nx/c Catalystsmentioning
confidence: 96%
“…The research revealed that the Fe−N 2 site was superior to the Fe−N 4 site because it had a lower interaction with *O 2 and *OH intermediates and accelerated electron transport [30] . Compared with the Co−N 2 C 2 and Co−N 4 sites, the ORR process proceeding over the Co−N 3 C 1 site has been revealed more energetically favorable [31] . The near‐Fermi electronic states of the Co−N 3 C 1 structure was distinct from that of the Co−N 2 C 2 and Co−N 4 structures, which not only facilitated the electronic hybridization with O 2 but also promoted the subsequent protonation of adsorbed O 2 *, thereby forming OOH*.…”
Section: Identification Of Active Sites For M−nx/c Catalystsmentioning
confidence: 96%
“…It is to note that DFT calculations revealed that CoN3C1 is the best electrocatalyst, as compared to Co-N2C2 and Co-N4, to exhibit near-Fermi electronic states, which promotes the electronic hybridization with O2 and the step of protonation of adsorbed O2*. [83] Wagh et al have designed single-atom coordinated hollow nano-spheroids of nitrogen-deficient carbon nitride by a two-step process, co-precipitation followed by annealing the metal- mA/cm² . [84] Figure 6: (a) The scheme and porous structures of the three model catalysts.…”
Section: Mof-derived Single-atom Catalystsmentioning
confidence: 97%
“…[81] (b) The STEM-EDS elemental maps and SEM images of Co/Zn-ZIF@ZIF-67. [83] The polarization curve and power density plot of the battery. [83] (d) The partial density of states (PDOS) of Fe, Co and Cu in FeSA@HNCNx, CoSA@HNCNx, and CuSA@HNCNx, respectively.…”
Section: Mof-derived Single-atom Catalystsmentioning
confidence: 99%
“…Single atom catalyst (SAC) has drawn an intensive research interest in heterogeneous catalysis because of its unique catalytic properties and maximized atom efficiency 1,2,3,4,5,6,7,8,9,10,11,12,13 . However, the electronic hybridization and polarization between single atoms and support often leads to a high valence state of supported single metal atoms, which significantly limit their catalytic applications in a variety of chemical conversions.…”
Section: Introductionmentioning
confidence: 99%